Asymptomatic and Symptomatic Patients With Non-severe Coronavirus Disease (COVID-19) Have Similar Clinical Features and Virological Courses: A Retrospective Single Center Study - Li, Yanli; Shi, Jie; Xia, Jianbo; Duan, Jie; Chen, Lijuan; Yu, Xudong; Lan, Weishun; Ma, Quanfu; Wu, Xufeng; Yuan, Yichong; Gong, Liyan; Yang, Xinghai; et al. (Frontiers in Microbiology, 2020)
The current outbreak of coronavirus disease 2019 (COVID-19) has been defined as a pandemic by the World Health Organization. We aimed to evaluate the clinical features and virological course of non-severe COVID-19 patients with or without symptoms who were admitted to a Chinese cabin hospital. In this retrospective single center study, we reviewed 252 laboratory-confirmed COVID-19 patients treated at one temporary cabin hospital in Wuhan, China. Demographic, clinical, serial chest computed tomography (CT), and serial viral test data were compared between asymptomatic and symptomatic patients. The association between clinical features and symptomatic status or patient referral status was analyzed. Among all 252 patients, 74 (29.4%) were asymptomatic and 138 (54.76%) had more than two family members who developed COVID-19. The probability for family clustering was similar between asymptomatic and symptomatic patients (59.70% versus 61.64%, P=0.79). Asymptomatic patients and symptomatic patients were equally likely to reach a virus-free state during their stay at the cabin hospital (93.15% versus 86.44%, P=0.13). The initial chest CT screening showed that 81 (32.1%) patients had no visible pneumonia, 52 (20.6%) had unilateral pneumonia, and 119 (47.2%) had bilateral pneumonia. Symptomatic patients had a higher chance to have bilateral pneumonia (P<0.0001) and were less likely to show improvement on the follow-up CT scan (P=0.0002). In total, 69 (27.4%) patients were referred to the designated hospital and only 23 (9.1%) patients were referred due to the progression of pneumonia. Non-severe COVID-19 patients can transmit the disease regardless of their symptomatic status. It is highly recommended that asymptomatic patients be identified and quarantined to eliminate the transmission of COVID-19